Role of Baclofen in Combination with Intensive Rehabilitation in Spastic Cerebral Palsy - Amin, Md Ruhul; Rahman, Sohely; Saha, Narayan; Hossain, Md Shahadat; Islam, Md Jahidul; Ahmed, Monzur; Chakraborty, Prasanta Kumar; Islam, Ferdous Ara (Journal of National Institute of Neurosciences Bangladesh, 2015)
Background: The treatment of cerebral palsy is multifactorial. Objective: In this study we find out the combined efficacy of baclofen and intensive rehabilitation in the treatment of spastic cerebral palsy. Methodology: This observational study was conducted over 30 patients in Dhaka Medical College Hospital from January 2011 to December 2011.The patient satisfying the inclusion and exclusion criteria was randomly enrolled in this study. They received Baclofen orally two times daily according to the body weight regularly in combination with intensive rehabilitation 1 hour daily five times a week for 24 weeks. All patients were followed up at 4 weeks interval and were evaluated for a total of 24 weeks. Result: Combination of Baclofen and intensive rehabilitation is effective in reducing tone in spastic cerebral palsy by using Modified Ashworth scale (p<0.05). Combination of Baclofen and intensive rehabilitation is also effective in joint angle improvement in spastic cerebral palsy measured by physician rating scale crouch (p<0.05) and foot contact, (p<0.05) and also improvement in gross motor function (p <0.05). Conclusion: For reduction of generalized spasticity regarding muscle tone, range of motion of the joint and improvement of gait in cerebral palsy patients, combination of Baclofen and intensive rehabilitation may be used. J. Natl Inst. Neurosci Bangladesh 2015;1(1):18-21